Increasing Production Efficiency Of an Extension Radio Program - Diane Relf; Mary Frank (Journal of Applied Communications, 1989)
Restrictions on time and money available for The Virginia Gardener radio program forced a re-evaluation of standard weekly or monthly production procedures. By changing to an annual system and using existing resources more efficiently, the program has become easier to produce and fits into station schedules more readily. The use of many guests has made it more interesting and diverse, and it is now widely used by Extension agents as well as radio stations. It is sent to 58 stations, which broadcast it an average of twice each week.